2006
DOI: 10.1021/pr060189z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Human Whole and Parotid Salivas Following Stimulation by Different Tastes

Abstract: Whole and parotid salivas, collected after stimulation with tastants, were analyzed by 2D electrophoresis and mass spectrometry. In whole saliva, the number of proteins affected by taste stimulation increased in the order sweet < umami < bitter < acid. Annexin A1 and calgranulin A, involved in inflammation, were over-represented after umami, bitter, and sour stimulations. Their low abundance or absence in parotid saliva after bitter stimulation suggested that they originated from other oral glands or tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 40 publications
5
67
2
4
Order By: Relevance
“…This implies that salivary response is adaptive, since the nature of the response is modulated by the "harmful" nature of the stimulus. This is supported by earlier finding showing that whole saliva proteome can be modified by the nature of the tastant with an overexpression of proteins involved in inflammatory response after stimulation by sour, bitter, and umami tastants but not after sweet (Neyraud et al 2006). Others reported a possible specific response of parotid saliva to tastant by a different protein pattern expression (Dawes 1984) or an increase of α-amylase concentration after drinking sugar solution but not after sham drinking, suggesting a metabolic adaptation of the parotid glands and their specific participation in the digestion and regulation of appetite (Harthoorn et al 2008).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…This implies that salivary response is adaptive, since the nature of the response is modulated by the "harmful" nature of the stimulus. This is supported by earlier finding showing that whole saliva proteome can be modified by the nature of the tastant with an overexpression of proteins involved in inflammatory response after stimulation by sour, bitter, and umami tastants but not after sweet (Neyraud et al 2006). Others reported a possible specific response of parotid saliva to tastant by a different protein pattern expression (Dawes 1984) or an increase of α-amylase concentration after drinking sugar solution but not after sham drinking, suggesting a metabolic adaptation of the parotid glands and their specific participation in the digestion and regulation of appetite (Harthoorn et al 2008).…”
Section: Introductionsupporting
confidence: 83%
“…Indeed, it has been reported that during perception of acid, the trigeminal free nerve ending are also stimulated (Lugaz et al 2005). Recently, an overexpression of protein secretion in whole saliva has been found after stimulation by tastants with the strongest modification of the whole saliva proteome after stimulation by acid (Neyraud et al 2006). The apparent oversecretion of protein in parotid saliva after stimulation by acid can be due to a synergic participation of the gustatory and trigeminal system.…”
Section: Taste and Proteinsmentioning
confidence: 99%
“…In 2DE profiles, the expression of some protein spots were observed to be differently changed following taste stimulation, these differences being dependent on the type of taste stimuli [84]. This suggests different adaptations of saliva to the five basic tastes.…”
Section: The Use Of Sds Page and 2-de In Salivary Proteome Study Relamentioning
confidence: 97%
“…Neyraud 26 analyzed both whole and parotid saliva composition following stimulation of the subjects with different tastes (sweet, bland, sour, acid) using trypsin digests and MALDI analyses. They discovered that two known proteins, calgranulin A and Annexin A1 were nearly absent in parotid saliva, indicating that they most likely originate from other oral tissues.…”
Section: Ferdinandy and Schulzmentioning
confidence: 99%